PERBANDINGAN ANTARA MSQ MIGRAINE SCREEN QUESTIONNAIRE VERSI INDONESIA DENGAN IDMIGRAINETM SEBAGAI ALAT SKRINING MIGREN - Yusuf Wibisono, Retno Jayantri Ketaren (NEURONA, 2014)
INTRODUCTION MIGRAINE IS A POPULAR DISEASE NOT ONLY FOUND IN ADULT POPULATION BUT ALSO IN SCHOOL CHILDREN AS IT IS THE FIFTH LEADING CAUSE OF HEALTH PROBLEMS IN CHILDREN AND ADOLESCENTS THERE IS AN INCREASE OF MIGRAINE PREVALENCE IN SCHOOL CHILDREN AGED 1519 YEARS OLD THEREFORE A VALIDATED MIGRAINE SCREENING TOOL IS NEEDED FOR EARLY DIAGNOSIS OF MIGRAINE IN SCHOOL CHILDREN